Feasibility of a Plasma Furnace for Methane Pyrolysis: Hydrogen and Carbon Production - Oday Daghagheleh; Johannes Schenk; Michael Andreas Zarl; Markus Lehner; Manuel Farkas; Heng Zheng (Energies, 2023)
The imperative to achieve a climate-neutral industry necessitates CO2-free alternatives for H2 production. Recent developments suggest that plasma technology holds promise in this regard. This study investigates H2 production by methane pyrolysis using a lab-scale plasma furnace, with the primary objective of achieving a high H2 yield through continuous production. The plasma furnace features a DC-transferred thermal plasma arc system. The plasma gas comprises Ar and CH4, introduced into the reaction zone through the graphite hollow cathode. The off-gas is channeled for further analysis, while the plasma arc is recorded by a camera installed on the top lid. Results showcase a high H2 yield in the range of up to 100%. A stable process is facilitated by a higher power and lower CH4 input, contributing to a higher H2 yield in the end. Conversely, an increased gas flow results in a shorter gas residence time, reducing H2 yield. The images of the plasma arc zone vividly depict the formation and growth of carbon, leading to disruptive interruptions in the arc, hence declining efficiency. The produced solid carbon exhibits high purity with a fluffy and fine structure. This paper concludes that further optimization and development of the process are essential to achieve stable continuous operation with a high utilization degree.